The role of tripartite social dialogue in facilitating a just transition: Experiences from selected countries - Oscar Molina (International Labour Organization (ILO), 2022)
This Working Paper analyses the role of tripartite social dialogue in supporting green workplaces and, more generally, promoting just transitions at enterprise level. The Working Paper explores the different mechanisms whereby social dialogue has contributed to governing, promoting and implementing policies and initiatives to achieve the above goals, with a particular focus on the role of National Social Dialogue Institutions (NSDIs). In doing so, the Working Paper also discusses the main challenges facing social partners regarding their involvement in these policies and processes, including the opportunities or obstacles created by the institutional framework, the type of technical capacities required and the articulation between different levels of social dialogue. Lastly, the Working Paper provides some policy pointers to enhance the role of social dialogue as a tool to sustain just transitions and extend green workplaces.
Keywords: 330; green jobs; social dialogue; enterprises